PENYELESAIAN KREDIT MACET AKIBAT DEBITUR WANPRESTASI DI BRI UNIT KRAKSAAN PROBOLINGGO - MOHAMMAD HENDRA (JUSTNESS - Jurnal Hukun dan Agama, 2022)
Abstrack Banks play a role as channeling funds for developing business activities and it is hoped that these businesses can strengthen the country's economy and support national development. Article 1 number 2 of Law Number 10 of 1998 concerning Banking. The problems studied in this study and the aim is to find out the terms and procedures for granting credit to the Probolinggo branch of kraksaan unit. And to find out the efforts made by the Probolinggo branch of the Kraksaan unit against bad loans due to default debtors. Based on the formulation of the problem and the objectives of this study, the method used in this study is the empirical juridical method using a case approach. The results of the study show that the main requirements include information on licensing data, financial data, and financial reports. Default resolution efforts include rescheduling, reconditioning, restructuring). Further settlement is carried out if the debtor defaults with immovable collateral with Mortgage installed and movable collateral with fiduciary guarantees. If there is no Mortgage or Fiduciary Right, then the BRI Kraksaan Unit will file a simple lawsuit at the Kraksaan District Court in accordance with Perma No. 4 of 2019 for Amendment to Perma No. 1 of 2015. And the auction proceeds as payment for the remaining outstanding achievements. Keywords: Bad Credit, Default